Hitro iskanje geometrijskih podatkov - Čapelnik, Sergej (Geodetski vestnik, 1998)
This paper presents an efficient approach to, and the advantages of, traversing a uniformly subdivided space pierced by a line segment. A voxel, as the basis constituent element of a uniformly subdivided space, is restricted to the form of a cube. The algorithm works in two steps. In the first step, the so-called Bresenham voxels are identified and, by comparing their position codes, their type of connectivity is determinated. To achieve the required connectivity between neighbouring voxels, the second step of the algorithm is applied to find the missing voxels. In this way, the algorithm efficiently switches between face-, edge- and vertex-connectivity. Although the algorithm works with floating-point precision, in computational terms, it is extremely efficient
Keywords: delitev prostora; geodezija; metode; prostor; računalniška grafika